ABOUT TIME, THE URBAN VILLAGE, AND DIGITAL DISRUPTIONS OF THE LONDON ROMANTIC COMEDY. - IDLE, HARRIET (Velvet Light Trap: A Critical Journal of Film & Television)
This article examines the disruptions seen between the London romantic comedy's depictions of pre- and post-digital urban space. Focusing on Richard Curtis's About Time (2013) as a pivotal case study, I analyze how the London rom-com has navigated the rapid integration of digital technologies within urban life since the genre's boom in the 1990s. I argue that the kinds of aesthetic and formal challenges to rom-com conventions seen in About Time in fact preserve the genre's central ideological underpinnings (and expectations of city space) in the face of the potentially unsettling or destructive impacts of digitization.